Conceptual Design And Implementation Of Electronic Spectacle Based Obstacle Detection For Visually Impaired Persons - Anuar , Mohamed Kassim; Takashi , Yasuno; Hiroshi, Suzuki; Mohd Aras, Mohd Shahrieel; Jaafar, Hazriq Izzuan; Jafar, Fairul Azni; Subramonian, Sivarao (The Japan Society of Mechanical Engineers, 2016)
-